2012
DOI: 10.1353/hpu.2012.0041
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics, Health, and Success at Obtaining Work among Latino Urban Day Laborers

Abstract: The stress of seeking work daily, separation from family, inadequate housing and lack of health care puts this population at increased risk for disease conditions associated with poor physical and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The fear of deportation is an ongoing threat in the daily life of an undocumented patient and this frequently leads to less participation in health care safety nets (11). Undocumented immigrants are often exploited in their workplace, compensated poorly, and may have the added stress of having to search for work on a daily basis (11). The traumatic separation from family and the persistent fear of deportation or detention can lead to severe mood disorders including post-traumatic stress disorder.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The fear of deportation is an ongoing threat in the daily life of an undocumented patient and this frequently leads to less participation in health care safety nets (11). Undocumented immigrants are often exploited in their workplace, compensated poorly, and may have the added stress of having to search for work on a daily basis (11). The traumatic separation from family and the persistent fear of deportation or detention can lead to severe mood disorders including post-traumatic stress disorder.…”
Section: Commentmentioning
confidence: 99%
“…For example, the patient’s wife was his only visitor during the hospital stay. Interestingly, a recent report showed that undocumented immigrants were less likely than U.S.-born individuals to be in a single person household (13% vs. 30%), suggesting that they are not always without support (11). …”
Section: Commentmentioning
confidence: 99%
“…In California, some 40,000 day labourers are estimated to seek work on any given day (Gonzalez 2007) though this number excludes those who come in and out the day labourer market seasonally (Nelson et al 2012). In California, about 80% of day labourers are presumed undocumented; primarily from Mexico and secondarily from Central America (Gonzalez 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the only national survey of day laborers, Valenzuela, Theodore, Meléndez, & Gonzalez (2006) estimated that their annual incomes rarely exceed $15,000. In a study conducted with 219 day laborers in San Francisco in 2009, two-thirds reported that they did not get enough to eat and more than half reported having poor or only fair health (Nelson, Schmotzer, Burgel, Crothers, & White, 2012). When day laborers were surveyed from two Northern California sites in 2008 (N = 102), high rates of stress were found for about 58% of the sample related to instability, relationship and communication difficulties, and alcohol/substance use (Duke, Bourdeau, & Hovey, 2010).…”
Section: Social and Economic Contextmentioning
confidence: 99%
“…A pilot study among day laborers in Washington State found a range of work-related, economic, and social stressors, along with biologic measures associated with allostatic load indicating a possible "wear and tear" effect that potentially link day laborers' difficult lives to negative consequences for their physical health (de Castro, Voss, Ruppin, Dominguez, & Seixas, 2010). Research focused on day laborers has consistently documented chronic lack of stable work and typically low-wage work, leading to economic instability and problems with housing, indebtedness, and family and friendship tensions (Duke et al, 2010;Negi, 2011;Nelson et al, 2012;Ordonez, 2012;Quesada, 2011;Walter, Bourgois, & Loinaz, 2004) The social context that imposes isolation and vulnerability includes hostile attitudes by host communities, a lack of policies that would permit documentation 392 P. A. WORBY AND K. C. ORGANISTA or work authorization for the majority, and frequent lack of basic resources such as healthcare programs. All of the above greatly constrain the ability to maintain health and well-being (LeClere & Lopez, 2012;Quesada, Hart, & Bourgois, 2011;Walter, Bourgois, Loinaz, & Schillinger, 2002).…”
Section: Social and Economic Contextmentioning
confidence: 99%